Investigating executive functions in children with severe speech and movement disorders using structured tasks - Stadskleiv, Kristine; von Tetzchner, Stephen; Batorowicz, Beata; van Balkom, Hans; Dahlgren-Sandberg, Annika; Renner, Gregor (Frontiers in Psychology, 2014)
Executive functions are the basis for goal-directed activity and include planning, monitoring, and inhibition, and language seems to play a role in the development of these functions. There is a tradition of studying executive function in both typical and atypical populations, and the present study investigates executive functions in children with severe speech and motor impairments who are communicating using communication aids with graphic symbols, letters and/or words. There are few neuropsychological studies of children in this group and little is known about their cognitive functioning, including executive functions. It was hypothesized that aided communication would tax executive functions more than speech. 29 children using communication aids and 27 naturally speaking children participated. Structured tasks resembling everyday activities, where the action goals had to be reached through communication with a partner, were used to get information about executive functions. The children a) directed the partner to perform actions like building a Lego tower from a model the partner could not see and b) gave information about an object without naming it to a person who had to guess what object it was. The executive functions of planning, monitoring and impulse control were coded from the children’s on-task behavior. Both groups solved most of the tasks correctly, indicating that aided communicators are able to use language to direct another person to do a complex set of actions. Planning and lack of impulsivity was positively related to task success in both groups. The aided group completed significantly fewer tasks, spent longer time and showed more variation in performance than the comparison group. The aided communicators scored lower on planning and showed more impulsivity than the comparison group, while both groups showed an equal degree of monitoring of the work progress. The results are consistent with the hypothesis that aided language tax executive functi